SOSIALISASI VAKSINASI COVID-19 DAN ADAPTASI KEBIASAAN BARU SEBAGAI UPAYA PENCEGAHAN PENYEBARAN VIRUS COVID-19 - Zea Riza Sinensis; Imam Shofwan; Iva Aprevia permata Bunda; Annisa Ratna Puspitasari; Wibowo Wibowo; Wildan Zamraza Nugraha (Bajang Institute, 2022)
The COVID-19 pandemic has caused many impacts in various fields such as education, economy, development and tourism. Therefore it is necessary to take precautions so that the spread does not get wider and ends soon. The purpose of the Real Work Lecture (KKN) work program is to provide education to the public through the dissemination of COVID-19 vaccination and adaptation of new habits, as an effort to prevent the spread of the COVID-19 virus in Gondoriyo Village, Bergas District, Semarang Regency. The COVID-19 vaccination is a form of effort made by the government to break the chain of COVID-19, with the intention that if vaccination coverage is high and evenly distributed in an area, it will form herd immunity. The method of socialization carried out is by placing posters and banners around Gondoriyo Village by complying with applicable health protocols according to government regulations. The socialization is expected to provide understanding to the public so that they continue to carry out government regulations to stop the spread of COVID-19. To support the government's vaccination efforts, it is also encouraging the adaptation of new habits in the community which includes 10 adaptations of new habits, namely using masks when traveling, washing hands with soap and running water, carrying hand sanitizer wherever traveling, maintaining a minimum distance of 1-2 meters, reducing mobility and reducing mobility. interaction, avoiding crowds, consuming vitamins and healthy nutritious food, keeping the environment clean, exercising at least 2-3 times a week, and getting enough rest. This socialization is expected to provide a better understanding of COVID-19 vaccination and Adaptation to New Habits (IMR) in the surrounding environment.